Fourteen days of bed rest induces a decline in satellite cell content and robust atrophy of skeletal muscle fibers in middle-aged adults - Arentson-Lantz, Emily J.; English, Kirk L.; Paddon-Jones, Douglas; Fry, Christopher S. (Journal of applied physiology (1985), 2016)
Bed rest, a ground-based spaceflight analog, induces robust atrophy of skeletal muscle, an effect that is exacerbated with increasing age. We examined the effect of 14 days of bed rest on skeletal muscle satellite cell content and fiber type atrophy in middle-aged adults, an understudied age demographic with few overt signs of muscle aging that is representative of astronauts who perform long-duration spaceflight. Muscle biopsies were obtained from the vastus lateralis of healthy middle-aged adults [ n = 7 (4 male, 3 female); age: 51 ± 1 yr] before (Pre-BR) and after (Post-BR) 14 days of bed rest. Immunohistochemical analyses were used to quantify myosin heavy chain (MyHC) isoform expression, cross-sectional area (CSA), satellite cell and myonuclear content, and capillary density. Peak oxygen consumption, knee extensor strength, and body composition were also measured Pre-BR and Post-BR. Post-BR MyHC type 2a fiber percentage was reduced, and mean CSA decreased in all fiber types (−24 ± 5%; P < 0.05). Satellite cell content was also reduced Post-BR (−39 ± 9%; P < 0.05), and the change in satellite cell content was significantly correlated with the change in mean fiber CSA ( r 2 = 0.60; P < 0.05). A decline in capillary density was observed Post-BR (−23 ± 6%; P < 0.05), and Post-BR capillary content was significantly associated with Post-BR peak aerobic capacity ( r 2 = 0.59; P < 0.05). A subtle decline in myonuclear content occurred during bed rest (−5 ± 1%; P < 0.05). The rapid maladaptation of skeletal muscle to 14 days of mechanical unloading in middle-aged adults emphasizes the need for robust countermeasures to preserve muscle function in astronauts.